Of Lymph Nodes and CLL Cells: Deciphering the Role of CCR7 in the Pathogenesis of CLL and Understanding Its Potential as Therapeutic Target - Cuesta-Mateos, Carlos; Brown, Jennifer R.; Terrón, Fernando; Muñoz-Calleja, Cecilia (Frontiers in Immunology, 2021)
The lymph node (LN) is an essential tissue for achieving effective immune responses but it is also critical in the pathogenesis of chronic lymphocytic leukemia (CLL). Within the multitude of signaling pathways aberrantly regulated in CLL the homeostatic axis composed by the chemokine receptor CCR7 and its ligands is the main driver for directing immune cells to home into the LN. In this literature review, we address the roles of CCR7 in the pathophysiology of CLL, and how this chemokine receptor is of critical importance to develop more rational and effective therapies for this malignancy.